Of men and manners essays historical and philosophical - Quinton, Anthony; Kenny, Anthony, 1931- (Oxford : Oxford University Press, 2011)
This is a collection of elegant and learned writings by the late Lord Quinton, one of the most prominent men of letters of the late 20th century. It ranges over the last 400 years of intellectual history and discusses freedom, morality, politics language, culture, and the relation between humans and animals.
Also issued in print format.
Description based on online resource; title from PDF title page (viewed on Jan. 21, 2012).
Includes bibliographical references and index.
Keywords: Intellectual life -- History; Ethics; Life